Cross-linking agent, preparation method thereof and variable-viscosity fracturing fluid
By using crosslinking agents formed by metal salts such as zirconium salts, aluminum salts and organic ligands such as alkanolamines, the viscosity adjustment range and poor temperature and shear resistance under high temperature and high shear conditions are solved. The problem of this problem has achieved low concentration crosslinking and delayed crosslinking characteristics, meeting the needs of large-scale sanding of deep shale oil and gas.
Patent Information
- Application Number
- CN202310984584.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-08-07
AI Technical Summary
The existing viscous fracturing liquid crosslinking agent has a narrow viscosity adjustment range under high temperature and high shear conditions, and has poor temperature and shear resistance, making it difficult to meet the large-scale sanding demand of deep shale oil and gas.
The crosslinking agent consisting of zirconium salt, aluminum salt, alkanolamine, α-hydroxycarboxylic acid and polyhydroxy compounds is used to form an organic aluminum-zirconium crosslinking agent through coordination complexation reaction to achieve low concentration crosslinking and delay crosslinking. Connection characteristics to reduce pipeline friction resistance.
Improve the viscosity of viscous fracturing fluid under high temperature and high shear, expand the viscosity adjustment window, enhance the temperature and shear resistance, meet the demand for large-scale sanding of deep shale oil and gas, and reduce construction costs and friction Obstacle.
Smart Images

Figure BDA0004380639190000021 
Figure BDA0004380639190000041 
Figure FDA0004380639180000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oilfield chemistry, and in particular relates to a cross-linking agent, a preparation method thereof and a variable viscosity fracturing fluid. Background Art
[0002] Variable viscosity fracturing fluid has the advantages of both drag reduction and sand carrying performance, and is easy to configure online. It is the preferred fluid for shale oil and gas reservoir development. At present, variable viscosity fracturing fluid is composed of a variety of additives such as suspended emulsion polymer thickener, clay stabilizer, and drainage agent. The amount of suspended emulsion thickener is 0.05% to 0.8%, the viscosity is 1 to 80mPa·s, and the temperature resistance is 140℃.
[0003] As exploration and development progresses in depth, the reservoir is buried deeper and deeper (vertical depth 4000-5000m), the temperature is getting higher and higher (140-160℃), and the closure stress is high (95-109MPa). In order to obtain better oil and gas production, it is necessary to further increase the construction displacement (18-22m 3 / min) and comprehensive sand-liquid ratio (10%-13%), but the existing variable viscosity fracturing fluid system has a narrow viscosity adjustment range, a high amount of suspension emulsion thickener, and poor temperature and shear resistance. For high-temperature deep shale oil and gas reservoirs with strong heterogeneity, large reservoir stress differences, and undeveloped fractures, it is difficult to meet the large-scale sand addition demand, which in turn affects the effective flow conductivity. Therefore, it is necessary to take measures to improve the viscosity and sand carrying capacity of the variable viscosity fracturing fluid system under high temperature and high shear.
[0004] As a key additive to improve the performance of fracturing fluid, cross-linking agent has become the first choice for the research of variable viscosity fracturing fluid system. The addition of cross-linking agent allows the suspended emulsion polymer to cross-link into a network jelly, and the variable viscosity fracturing fluid is converted from a self-cross-linking type to a cross-linking type, which can greatly improve the temperature and shear resistance of the system. However, the cross-linking agent of the variable viscosity fracturing fluid in the prior art is generally synthesized from zirconium salts or boron salts, and the cross-linking time is relatively short, resulting in higher pipeline friction resistance, and the ligand types are relatively single, with fewer cross-linking sites, and low-concentration cross-linking cannot be achieved. Therefore, how to control the cross-linking time through the cross-linking agent to reduce pipeline friction resistance, and at the same time increase the cross-linking bonding density points to achieve low-concentration thickener cross-linking, improve the system's temperature and shear resistance, and increase the sand addition strength, thereby achieving the required reservoir transformation effect, is one of the problems that technicians in this field urgently need to solve. Summary of the invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide a cross-linking agent, a preparation method thereof and a variable viscosity fracturing fluid. The cross-linking agent is applied to the variable viscosity fracturing fluid to achieve low-concentration cross-linking and reduce construction costs. At the same time, it has the characteristic of delayed cross-linking, which can reduce pipeline friction and improve the temperature and shear resistance of the system, thereby meeting the requirements for large-scale sand addition in deep shale oil and gas.
[0006] The present invention provides a cross-linking agent, which is formed by mixed components; the mixed components include metal salts, organic ligands, surfactants and solvents;
[0007] The metal salts include zirconium salts and aluminum salts;
[0008] The organic ligands include alkanolamines, α-hydroxycarboxylic acids and polyhydroxy compounds.
[0009] Preferably, the mixed components include:
[0010]
[0011] Preferably, the mass ratio of the zirconium salt to the aluminum salt is (3-5):1;
[0012] The mass ratio of the alkanolamine, α-hydroxycarboxylic acid and polyhydroxy compound is (8-12): (12-15): (5-8).
[0013] Preferably, the alkanolamine is selected from one or more of diethanolamine, triethanolamine and triisopropanolamine;
[0014] The α-hydroxycarboxylic acid is selected from one or more of citric acid, lactic acid, glycolic acid and tartaric acid;
[0015] The polyhydroxy compound is selected from polyols and / or polyhydroxy carboxylates;
[0016] The polyol is selected from one or more of sorbitol, xylitol, mannitol, dipentaerythritol, ethylene glycol and glycerol;
[0017] The polyhydroxycarboxylate is selected from sodium gluconate and / or sodium citrate.
[0018] Preferably, the organic ligand further comprises a small molecule aldehyde; the mass ratio of the small molecule aldehyde to the alkanolamine is (5-8):(8-12).
[0019] Preferably, the small molecule aldehyde is selected from one or more of formaldehyde, acetaldehyde and glyoxal.
[0020] Preferably, the aluminum salt is selected from one or more of aluminum chloride, aluminum sulfate and aluminum citrate;
[0021] The zirconium salt is selected from one or more of zirconium oxychloride, zirconium nitrate, zirconium sulfate and zirconium chloride;
[0022] The surfactant is selected from one or more of sodium dodecylbenzene sulfonate, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, sodium lauryl sulfate and propylene glycol block polyether;
[0023] The solvent is water and an alcohol solvent; the mass ratio of the water to the alcohol solvent is (2-5):1.
[0024] Preferably, a pH regulator is also included; the pH regulator makes the pH value of the mixed components 4-7; the pH regulator is selected from one or more of sodium carbonate, sodium bicarbonate and sodium hydroxide.
[0025] The present invention also provides a method for preparing a cross-linking agent, comprising the following steps:
[0026] The metal salt, surfactant and solvent are mixed, and then heated to react, and then an organic ligand is added to continue the reaction to obtain a cross-linking agent.
[0027] The present invention also provides a variable viscosity fracturing fluid, comprising the above cross-linking agent.
[0028] The present invention provides a crosslinking agent, which is formed by mixed components; the mixed components include metal salts, organic ligands, surfactants and solvents; the metal salts include zirconium salts and aluminum salts; the organic ligands include alkanolamines, α-hydroxycarboxylic acids and polyhydroxy compounds. Compared with the prior art, the present invention uses zirconium salts, aluminum salts and organic ligands such as alcoholamines and organic acids to form an organic aluminum-zirconium crosslinking agent through coordination and complexation reactions, which can effectively reduce the amount of suspended emulsion polymer thickeners, achieve ultra-low concentration (0.2% suspended emulsion polymer thickener) crosslinking, and has the characteristic of delayed crosslinking, which can effectively reduce pipeline construction friction resistance, and at the same time can also improve the viscosity of the variable viscosity fracturing fluid system under high temperature and high shear, so that its viscosity adjustment window is wide and its adaptability is strong, which meets the requirements of online mixing and large-scale sand addition of deep shale oil and gas, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a graph showing the test results of the high temperature and shear resistance of the cross-linking agent prepared in Example 1 of the present invention;
[0030] Figure 2 This is a graph showing the test results of the high temperature and shear resistance of the cross-linking agent prepared in Example 2 of the present invention;
[0031] Figure 3 This is a graph showing the test results of the high temperature and shear resistance of the cross-linking agent prepared in Example 3 of the present invention;
[0032] Figure 4 This is a photo of the crosslinking performance test of the crosslinking agent prepared in Example 2 of the present invention and 0.2% suspension emulsion polymer thickener;
[0033] Figure 5 This is a photo of the crosslinking performance test of the crosslinking agent prepared in Comparative Example 1 of the present invention and 0.2% and 0.4% suspension emulsion polymer thickeners. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0035] The invention provides a crosslinking agent, which is formed by mixed components; the mixed components include metal salts, organic ligands, surfactants and solvents; the metal salts include zirconium salts and aluminum salts; the organic ligands include alkanolamines, alpha-hydroxycarboxylic acids and polyhydroxy compounds.
[0036] According to the present invention, the mixed components preferably include:
[0037]
[0038] The cross-linking agent provided by the present invention uses zirconium and aluminum as central ions, and balances the cross-linking and temperature resistance of the system through the complementary properties of the two central ions, thereby maximizing the temperature resistance of the system while satisfying room temperature cross-linking. In the present invention, the mass ratio of the zirconium salt to the aluminum salt is preferably (3-5):1, more preferably (3-4.5):1, more preferably (3-4):1, and most preferably (3.3-4):1; in the embodiments provided by the present invention, the mass ratio of the zirconium salt to the aluminum salt is specifically 10:3, 12:3 or 15:4; the zirconium salt can be any zirconium salt known to those skilled in the art without any special restrictions, and in the present invention, it is preferably one or more of zirconium oxychloride, zirconium nitrate, zirconium sulfate and zirconium chloride; the aluminum salt can be any aluminum salt known to those skilled in the art without any special restrictions, and in the present invention, it is preferably one or more of aluminum trichloride, aluminum sulfate and aluminum citrate; in the cross-linking agent provided by the present invention, the content of the metal salt in the mixed component is preferably 8-25 parts by weight, more preferably 10-20 parts by weight, and more preferably 13-19 parts by weight; in the embodiments provided by the present invention, the content of the metal salt in the mixed component is specifically 13 parts by weight, 15 parts by weight or 19 parts by weight.
[0039] According to the present invention, the content of the organic ligand in the mixed component is preferably 20 to 45 parts by weight, more preferably 25 to 40 parts by weight; in the embodiments provided by the present invention, the content of the organic ligand in the mixed component is specifically 25 parts by weight, 35 parts by weight or 40 parts by weight; the organic ligand in the present invention comprises alkanolamine, α-hydroxycarboxylic acid and polyhydroxy compound; the mass ratio of the alkanolamine, α-hydroxycarboxylic acid and polyhydroxy compound is preferably (8 to 12): (12 to 15): (5 to 8); in the embodiments provided by the present invention; the mass ratio of the alkanolamine, α-hydroxycarboxylic acid and polyhydroxy compound is specifically 8:12:5, 10:12:8 or 12:15 : 5; wherein, the alcohol amine ligand can emulsify and thicken the solution, and increase the temperature resistance of the cross-linked jelly; the carbon number of the alkyl group in the alkanolamine is preferably 1 to 5, more preferably 2 to 4, and more preferably 2 or 3; in the present invention, the alkanolamine preferably includes but is not limited to one or more of diethanolamine, triethanolamine and triisopropanolamine; α-hydroxycarboxylic acid ligands can improve the temperature resistance and stability of the cross-linking agent; the α-hydroxycarboxylic acid preferably includes but is not limited to one or more of citric acid, lactic acid, glycolic acid and tartaric acid; the polyhydroxy compound is preferably a polyol and / or a polyhydroxycarboxylate; the polyol preferably includes but is not limited to sorbitol, xylitol, mannitol, dipentaerythritol One or more of alcohol, ethylene glycol and glycerol; polyol ligands can increase the solubility of ligands and solutions, promote the formation of central ion-ligand coordination bonds, increase the effective content of crosslinking agents, achieve low-concentration crosslinking and improve the temperature resistance of the system, and the alcohol ligand contains dipentaerythritol with a branched structure, which can increase the molecular weight of the crosslinking agent and the branched structure has a delayed crosslinking function, better control the viscosity of the system, and effectively reduce the friction resistance of pipeline construction; the polyhydroxy carboxylate preferably includes but is not limited to sodium gluconate and / or sodium citrate; the carboxylate ligand has a good affinity for the crosslinking agent atom, which can improve the stability of the crosslinking agent; in the present invention, the organic ligand preferably also includes a small molecule aldehyde; the small The mass ratio of the molecular aldehyde to the alkanolamine is preferably (5-8): (8-12), more preferably (5-8): (10-12); the small molecule aldehyde preferably includes but is not limited to one or more of formaldehyde, acetaldehyde and glyoxal; the small molecule aldehyde ligand has multiple strongly coordinated oxygen atoms and nitrogen atoms, which can be combined with the central ion at multiple sites, thereby increasing the crosslinking density of the crosslinker, thereby achieving low-concentration crosslinking, and greatly improving the crosslinking performance and temperature resistance of the system, and the carbonyl group of the small molecule aldehyde and the carboxyl group of the α-hydroxycarboxylic acid have a synergistic effect, so that the oxygen of the carboxyl group and the carbonyl group becomes an electron-rich nucleophilic reagent, which is complexed with the central ion (electrophilic reagent) that can provide an empty orbital, making the crosslinker product performance more stable.
[0040] According to the present invention, the content of the surfactant in the mixed component is preferably 1.5 to 2.5 parts by weight, more preferably 2 parts by weight; the surfactant can be a surfactant well known to those skilled in the art, without special restrictions, and preferably includes but is not limited to one or more of sodium dodecylbenzene sulfonate, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, sodium lauryl sulfate and propylene glycol block polyether.
[0041] According to the present invention, the content of the solvent in the mixed components is preferably 40 to 65 parts by weight, more preferably 45 to 60 parts by weight, and even more preferably 50 to 60 parts by weight; the solvent is preferably water and an alcohol solvent; the mass ratio of water to alcohol solvent is preferably (2 to 5):1, more preferably (3 to 5):1, even more preferably (3.5 to 4.5):1, and most preferably 4:1.
[0042] According to the present invention, the mixed components preferably also include a pH regulator; the pH regulator makes the pH value of the mixed components 4 to 7, more preferably 4.5 to 6.5, and more preferably 5 to 6; in the present invention, preferably, the content of the pH regulator in the mixed components is preferably 2 to 6 parts by weight, more preferably 2 to 5 parts by weight, and more preferably 2 to 4 parts by weight; the pH regulator preferably includes but is not limited to one or more of sodium carbonate, sodium bicarbonate and sodium hydroxide.
[0043] The present invention utilizes zirconium salt, aluminum salt and organic ligands such as alcohol amine and organic acid to form an organic aluminum zirconium crosslinking agent through coordination complex reaction, which can effectively reduce the dosage of suspension emulsion polymer thickener, achieve ultra-low concentration (0.2% suspension emulsion polymer thickener) crosslinking, and has the characteristic of delayed crosslinking, which can effectively reduce pipeline construction friction resistance, and at the same time can also improve the viscosity of the variable viscosity fracturing fluid system under high temperature and high shear, so that the viscosity adjustment window is wide and the adaptability is strong, which meets the requirements of online mixing and large-scale sand addition of deep shale oil and gas, and has good application prospects.
[0044] The present invention also provides a method for preparing the crosslinking agent, comprising the following steps: mixing a metal salt, a surfactant and a solvent, heating them for reaction, and then adding an organic ligand for further reaction to obtain the crosslinking agent.
[0045] The present invention has no special restrictions on the sources of all raw materials, and any raw materials available on the market can be used; the salts, surfactants, solvents and organic ligands are the same as those described above and will not be described in detail here.
[0046] In the present invention, it is preferred to first deoxygenate the solvent; the deoxygenation method may be a method well known to those skilled in the art, without any particular limitation, and in the present invention, preferably, deoxygenation is carried out by introducing a protective gas under stirring; the stirring speed is preferably 230 to 430 r / min, more preferably 280 to 380 r / min, and further preferably 330 to 350 r / min; the protective atmosphere may be a protective gas well known to those skilled in the art, without any particular limitation, and in the present invention, nitrogen is preferably used; the time for introducing the protective gas is preferably 10 to 40 min, more preferably 20 to 30 min.
[0047] Then, metal salt and surfactant are added and mixed, and heated for reaction; in the present invention, it is further preferred that the surfactant is added and stirred first, and then the metal salt is added and mixed; the stirring and mixing speed is preferably 230-430 r / min, more preferably 280-380 r / min, and more preferably 330-350 r / min; the stirring and mixing time is preferably 1-5 min, more preferably 2-4 min, and more preferably 3 min; the mixing time is preferably 5-15 min, more preferably 7-13 min, more preferably 8-12 min, more preferably 9-11 min, and most preferably 10 min; the mixing is preferably carried out under stirring; the stirring speed is preferably 230-430 r / min, more preferably 280-380r / min, and even more preferably 330-350r / min; the mixing temperature is preferably 20°C-40°C, more preferably 25°C-35°C, and even more preferably 30°C; the heating reaction temperature is preferably 50°C-100°C, more preferably 60°C-90°C, even more preferably 70°C-80°C, and most preferably 75°C; the heating reaction time is preferably 0.3-0.8h, more preferably 0.4-0.6h, and even more preferably 0.5h; the heating rate of the heating reaction is preferably 0.2-1.4°C / min, more preferably 0.4-1.2°C / min, even more preferably 0.6-1.0°C / min, and most preferably 0.7-0.9°C / min.
[0048] Then add an organic ligand to continue the reaction to obtain a cross-linking agent; in the present invention, a pH adjuster is preferably added after adding the organic ligand; the type and amount of the pH adjuster are the same as described above and will not be repeated here; the time for continuing the reaction is preferably 0.5 to 4 hours, more preferably 1 to 3 hours, and more preferably 1.5 to 2 hours.
[0049] In the present invention, the addition time of the organic ligand can also be adjusted according to the properties of the organic ligand. If the organic ligand includes a low-temperature organic ligand, it can be added before the heating reaction; if the organic ligand includes a high-temperature organic ligand, it can be added after the heating reaction.
[0050] The cross-linking agent prepared in the present invention is generally a light yellow transparent liquid, which can form a gel with the suspension emulsion polymer thickener to increase the temperature and shear resistance of the system, thereby facilitating sand carrying, and has a certain delayed cross-linking property. The cross-linking effect occurs in the wellbore, effectively reducing friction, and can achieve low-concentration cross-linking, thereby reducing liquid costs.
[0051] The present invention also provides a variable viscosity fracturing fluid, comprising the above cross-linking agent.
[0052] The volume of the cross-linking agent is preferably 0.1% to 1% of the volume of the variable viscosity fracturing fluid, more preferably 0.1% to 0.5%, further preferably 0.2% to 0.4%, and most preferably 0.3%.
[0053] The cross-linking agent in the variable viscosity fracturing fluid provided by the present invention is cross-linked under neutral conditions. The cross-linking agent exists as a coordination bond type complex under neutral conditions. Only under this condition can it combine with groups such as carboxyl groups and amide groups on the polymer chain to form a more stable cross-linked gel.
[0054] According to the present invention, the variable viscosity fracturing fluid preferably also includes a fracturing fluid base fluid; the fracturing fluid base fluid includes water, an emulsion polymer thickener, a drainage aid and a clay stabilizer.
[0055] Among them, the emulsion polymer thickener is preferably a suspended emulsion polymer thickener; the solid content of the suspended emulsion polymer thickener is preferably 20% to 50%, more preferably 30% to 45%, more preferably 35% to 45%, and most preferably 40%; the emulsion polymer thickener preferably includes polymer powder, oil phase, emulsifier, thickening stabilizer and water; the polymer powder is preferably a tetrapolymer of acrylic acid, acrylamide, N,N-dimethylacrylamide, and 2-acrylamide-2-methylpropanesulfonic acid; the oil phase is preferably white oil; the emulsifier is preferably Tween, more preferably Tween 81; the thickening stabilizer is preferably one or more of sodium bentonite, xanthan gum and sodium carboxymethyl cellulose.
[0056] The extrusion aid may be any extrusion aid known to those skilled in the art without any particular limitation. In the present invention, it preferably includes but is not limited to one or more of alkyl ethoxylates, alkylphenol polyoxyethylene ethers and alkyl polyglycoside surfactants.
[0057] The clay stabilizer can be any clay stabilizer known to those skilled in the art without any particular limitation. In the present invention, it preferably includes but is not limited to two composites of KCl, NH4Cl, tetramethylammonium chloride, benzyltrimethylammonium chloride, and diallyldimethylammonium chloride.
[0058] According to the present invention, the volume ratio of water, emulsion polymer thickener, drainage agent and clay stabilizer in the fracturing fluid base fluid is preferably 1000: (5-20): (0.5-5): (0.5-3), more preferably 1000: (10-15): (2-4): (1-2), and even more preferably 1000: 12: 3: 1.
[0059] The fracturing fluid base fluid can be prepared according to methods well known to those skilled in the art without any special restrictions. In the present invention, it is preferred that: water, an emulsion polymer thickener, a drainage agent and a clay stabilizer are mixed to obtain a fracturing fluid base fluid; the mixing is preferably carried out under stirring conditions; the mixing time is preferably 20s to 90s, more preferably 30 to 80s, and even more preferably 60s.
[0060] The cross-linking agent provided by the present invention can form a gel with a suspension emulsion thickener, and has a wide viscosity adjustment window, which is helpful to enhance the temperature resistance of the system and is beneficial to sand carrying; the cross-linking agent series products increase the cross-linking density point, which can effectively reduce the amount of suspension emulsion polymer thickener, and achieve ultra-low concentration (0.2% suspension emulsion polymer thickener) cross-linking; and have the characteristic of delayed cross-linking, which can effectively reduce the friction resistance of pipeline construction and reduce the construction pressure.
[0061] The present invention also provides a method for preparing the above-mentioned variable viscosity fracturing fluid, comprising: mixing a fracturing fluid base fluid with a cross-linking agent to obtain a variable viscosity fracturing fluid; the fracturing fluid base fluid and the cross-linking agent are the same as described above and will not be described in detail here.
[0062] In the embodiment provided by the present invention, the preparation method of the variable viscosity fracturing fluid is specifically as follows: 1000mL of tap water is measured and poured into the Wu Yin mixer, and the speed of the Wu Yin mixer is adjusted until the vortex formed by the liquid can see the top of the central axis of the mixer blade. Then, 12mL of the suspended emulsion polymer thickener is measured and quickly added to the stirring cup, and 3mL of the drainage agent and 1mL of the clay stabilizer are added in sequence, and stirred for 60s to obtain the fracturing fluid base liquid; 100mL of the above fracturing fluid base liquid is taken, 0.3mL of the cross-linking agent is added, and stirred evenly to obtain the variable viscosity fracturing fluid.
[0063] In order to further illustrate the present invention, the following describes in detail a cross-linking agent, a preparation method thereof and a variable viscosity fracturing fluid in combination with embodiments.
[0064] The reagents used in the following examples are all commercially available.
[0065] Example 1
[0066] The components of the cross-linking agent are: in parts by weight, 10 parts of zirconium salt, 3 parts of aluminum salt, 25 parts of organic ligand (8 parts of alkanolamine, 12 parts of α-hydroxycarboxylic acid, 5 parts of polyhydroxycarboxylate), 2 parts of surfactant, 4 parts of pH regulator, and 50 parts of solvent (10 parts of organic solvent and 40 parts of water); the zirconium salt is zirconium oxychloride octahydrate, the aluminum salt is aluminum trichloride, the alkanolamine is diethanolamine, the α-hydroxycarboxylic acid is lactic acid, the polyhydroxycarboxylate is sodium citrate, the surfactant is sodium dodecyl sulfate, the organic solvent is glycerol, and the pH regulator is sodium hydroxide.
[0067] The preparation method of the cross-linking agent is as follows: the temperature is set to 30°C and the rotation speed is 330r / min, the solvent is deoxygenated by nitrogen for 30 minutes, a surfactant is added to the solvent, the mixture is stirred for 3 minutes, and then zirconium salt and aluminum salt are added, the temperature and the rotation speed are kept unchanged and the stirring is continued for 10 minutes until the mixture is dissolved; the mixture is heated to 75°C at a heating rate of 0.8±0.1°C / min, the stirring is continued for 0.5h, a high-temperature organic ligand is added to continue the reaction, and after mixing, the pH value of the mixed solution is adjusted to between 5.0 and 6.0 with a pH adjuster, and the reaction is continued for 1.5h to obtain a cross-linking agent.
[0068] Example 2
[0069] The components of the cross-linking agent are: in parts by weight, 12 parts of zirconium salt, 3 parts of aluminum salt, 35 parts of organic ligand (10 parts of alkanolamine, 12 parts of α-hydroxycarboxylic acid, 8 parts of polyol, 5 parts of small molecule aldehyde), 2 parts of surfactant, 4 parts of pH regulator, 50 parts of solvent (10 parts of organic solvent, 40 parts of water); the zirconium salt is zirconium oxychloride octahydrate, the aluminum salt is aluminum trichloride, the alkanolamine is triethanolamine, the α-hydroxycarboxylic acid is lactic acid, the polyol is ethylene glycol and dipentaerythritol (mass ratio is 3:5), the small molecule aldehyde is formaldehyde, the surfactant is sodium dodecyl sulfate, the organic solvent is propylene glycol, and the pH regulator is sodium hydroxide.
[0070] The preparation method of the cross-linking agent is as follows: the temperature is set to 30°C and the rotation speed is 330r / min, after the solvent is deoxygenated by nitrogen for 30 minutes, a surfactant is added to the solvent, the mixture is stirred for 3 minutes, and then zirconium salt and aluminum salt are added, the temperature and the rotation speed are kept unchanged and the stirring is continued for 10 minutes until the mixture is dissolved; the mixture is heated to 75°C at a heating rate of 0.8±0.1°C / min, the stirring is continued for 0.5h, a high-temperature organic ligand is added to continue the reaction, and after mixing, the pH value of the mixed solution is adjusted to between 5.0 and 6.0 with a pH adjuster, and the reaction is continued for 2h to obtain a cross-linking agent.
[0071] Example 3
[0072] The components of the cross-linking agent are: in parts by weight, 15 parts of zirconium salt, 4 parts of aluminum salt, 40 parts of organic ligand (12 parts of alkanolamine, 15 parts of α-hydroxycarboxylic acid, 5 parts of polyhydroxycarboxylate, 8 parts of small molecule aldehyde), 2 parts of surfactant, 3 parts of pH regulator, and 60 parts of solvent (15 parts of organic solvent and 45 parts of water); the zirconium salt is zirconium oxychloride octahydrate, the aluminum salt is aluminum trichloride, the alkanolamine is triethanolamine, the α-hydroxycarboxylic acid is lactic acid, the polyhydroxycarboxylate is sodium citrate, the small molecule aldehyde is formaldehyde, the surfactant is sodium dodecyl sulfate, the organic solvent is propylene glycol, and the pH regulator is sodium hydroxide.
[0073] The preparation method of the cross-linking agent is as follows: the temperature is set to 30°C and the rotation speed is set to 330r / min, the solvent is deoxygenated by nitrogen for 30 minutes, a surfactant is added to the solvent, the mixture is stirred for 3 minutes, and then zirconium salt and aluminum salt are added, the temperature and rotation speed are kept unchanged and stirring is continued for 10 minutes until the mixture is dissolved; the mixture is heated to 75°C at a heating rate of 0.8±0.1°C / min, stirring is continued for 0.5h, a high-temperature organic ligand is added to continue the reaction, and after mixing, the pH value of the mixed solution is adjusted to between 6.0 with a pH adjuster, and the reaction is continued for 2h to obtain a cross-linking agent.
[0074] Comparative Example 1
[0075] The components of the cross-linking agent are: in parts by weight, 12 parts of zirconium salt, 3 parts of aluminum salt, 35 parts of organic ligand (20 parts of alkanolamine, 15 parts of α-hydroxycarboxylic acid), 2 parts of surfactant, 4 parts of pH regulator, and 50 parts of solvent (10 parts of organic solvent and 40 parts of water); the zirconium salt is zirconium oxychloride octahydrate, the aluminum salt is aluminum trichloride, the alkanolamine is triethanolamine, the α-hydroxycarboxylic acid is lactic acid, the surfactant is sodium dodecyl sulfate, the organic solvent is propylene glycol, and the pH regulator is sodium hydroxide.
[0076] The preparation method of the cross-linking agent is as follows: the temperature is set to 30°C and the rotation speed is 330r / min, the solvent is deoxygenated by nitrogen for 30 minutes, a surfactant is added to the solvent, the mixture is stirred for 3 minutes, and then zirconium salt and aluminum salt are added, the temperature and the rotation speed are kept constant and the stirring is continued for 10 minutes until the mixture is dissolved; the mixture is heated to 75°C at a heating rate of 0.8±0.1°C / min, the stirring is continued for 0.5h, and the high-temperature organic ligand is continued to be added for reaction, and after mixing, the pH value of the mixed solution is adjusted to between 5.0 and 6.0 with a pH adjuster, and the reaction is continued for 2h to obtain a cross-linking agent.
[0077] Performance Testing
[0078] Preparation of base liquid: 1000mL of tap water was measured and poured into the Wu Yin mixer, and the speed of the Wu Yin mixer was adjusted until the vortex formed by the liquid could see the top of the central axis of the mixer blade, and then 12mL of suspension emulsion polymer thickener (self-made, prepared according to Example 2 of CN 114456795 A) was measured and added in sequence, and 3mL of drainage agent (self-made, 5 parts by weight of perfluoroalkyl polyoxyethylene ether CF16400 of Jinan Qifu New Material Technology Co., Ltd., 7 parts by weight of alkylphenol polyoxyethylene ether OP-10 of Jiangsu Hai'an Petrochemical Plant, 3 parts by weight of coconut oil alkyl glucoside APG of Jiangsu Hai'an Petrochemical Plant, 85 parts by weight of water) was added, and 1mL of clay stabilizer (Beijing Baofengchun Petroleum Technology Co., Ltd., a compound of KCl and tetramethylammonium chloride) was added. After 1 minute, stirring was stopped to obtain a base liquid.
[0079] 100 mL of the above base fluid was taken, and 0.3 mL of the cross-linking agent prepared in Examples 1 to 3 was added respectively, and after stirring evenly, different variable viscosity fracturing fluids were obtained.
[0080] The high temperature and shear resistance of the above-mentioned variable viscosity fracturing fluid was tested using an RS300 high temperature and high pressure rheometer. The heating rate was controlled to be 3.0℃ / min±0.2℃ / min, the experimental temperature was 180℃, and the shear rate was 170s. -1 , shear time is 90min; test results: at 180℃, 170s -1 After 90 minutes of shearing, the rheological viscosities of the crosslinking agents prepared in Examples 1 to 3 were 138 mPa.s, 200 mPa.s, and 175 mPa.s, respectively. Figure 1 to Figure 3 As shown, both can meet the requirement of viscosity ≥ 50 mPa.s in the industry standard SY / T 7627-2021 "Technical Requirements for Water-Based Fracturing Fluids". At the same time, it can be seen that the cross-linking agent prepared in Example 2 has better performance.
[0081] The crosslinking agent prepared in Example 2, 0.2% suspension emulsion polymer thickener and water were used to prepare a crosslinked gel. The amount of the crosslinking agent was 0.3% to test the crosslinking performance. The test results Figure 4 As shown, a hanging gel can be formed. Comparative Example 1 does not add polyols and small molecule aldehyde ligands, and the amount of crosslinking agent prepared is 0.3%, and 0.2% and 0.4% suspension emulsion polymer thickeners are used to prepare crosslinked gels. The test results Figure 5 As shown, it can be cross-linked with 0.2% suspension emulsion polymer but not hangable, and can form hangable jelly with 0.4% suspension emulsion polymer. Both have white particles that are incompatible, which cause great damage to the reservoir.
[0082] Compared with CN 110003877A "A kind of clean viscous and slippery water resistant to high mineralization, cross-linking agent, viscosity-changing drag-reducing agent and preparation method" and CN 115287054A "Organoaluminum cross-linking agent and preparation method thereof and application in continuous mixed fracturing fluid", the cross-linking agent prepared by the embodiment of the present invention has a simpler process, and small molecule alkanolamines and aldehydes are added to the ligand, which have multiple strongly coordinated oxygen atoms and nitrogen atoms and can be combined with multiple sites of the central ion, greatly improving the cross-linking performance of the system (cross-linking with 0.2% suspension emulsion polymer thickener can be hanged) and temperature resistance (1.2% suspension emulsion polymer thickener, 180°C, after continuous shearing for 90 minutes, viscosity>100mPa.s), which can meet the large-scale sanding needs of deep shale oil and gas.
[0083] The crosslinking agent provided by the invention has two composite central ions with complementary properties, which can better balance the crosslinking and temperature resistance of the system, and maximize the temperature resistance of the system under the premise of meeting the crosslinking at room temperature; the ligand is a small molecule ligand with small steric hindrance and multiple binding sites, which can realize multi-head crosslinking, and a series of crosslinking agent products are formed by changing the type of ligand and the reaction temperature, reaction time, pH and other conditions, so that the crosslinking agent can form a gel with a suspension emulsion polymer thickener, and the viscosity adjustment window is wide, the temperature resistance can reach 180°C, and it is conducive to carrying sand; the dosage of the suspension emulsion polymer thickener can be effectively reduced to achieve ultra-low concentration (0.2% suspension emulsion polymer thickener) crosslinking; the crosslinking agent has the characteristic of delaying crosslinking, and can effectively reduce the friction resistance of pipeline construction and reduce the construction pressure.
[0084] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention, but the present invention is not limited thereto. Those skilled in the art can understand that within the technical concept of the present invention, the technical solution of the present invention can be modified, or some technical features can be combined in any other way. These modifications or combinations do not make the essence of the corresponding technical solution deviate from the spirit and scope of each implementation of the technical solution of the present invention, and should be regarded as the contents disclosed by the present invention, which belong to the protection scope of the present invention.
Claims
1. A cross-linking agent, characterized in that The mixture is formed by mixed components; the mixed components include metal salt, organic ligand, surfactant and solvent; The metal salts include zirconium salts and aluminum salts; The organic ligands include alkanolamines, α-hydroxycarboxylic acids and polyhydroxy compounds.
2. The crosslinking agent according to claim 1, characterized in that The mixed components include:
3. The crosslinking agent according to claim 1, characterized in that The mass ratio of the zirconium salt to the aluminum salt is (3-5):1; The mass ratio of the alkanolamine, α-hydroxycarboxylic acid and polyhydroxy compound is (8-12): (12-15): (5-8).
4. The crosslinking agent according to claim 1, characterized in that The alkanolamine is selected from one or more of diethanolamine, triethanolamine and triisopropanolamine; The α-hydroxycarboxylic acid is selected from one or more of citric acid, lactic acid, glycolic acid and tartaric acid; The polyhydroxy compound is selected from polyols and / or polyhydroxy carboxylates; The polyol is selected from one or more of sorbitol, xylitol, mannitol, dipentaerythritol, ethylene glycol and glycerol; The polyhydroxycarboxylate is selected from sodium gluconate and / or sodium citrate.
5. The cross-linking agent according to claim 1, characterized in that The organic ligand also includes a small molecule aldehyde; the mass ratio of the small molecule aldehyde to the alkanolamine is (5-8): (8-12).
6. The cross-linking agent according to claim 5, characterized in that The small molecule aldehyde is selected from one or more of formaldehyde, acetaldehyde and glyoxal.
7. The cross-linking agent according to claim 1, characterized in that The aluminum salt is selected from one or more of aluminum chloride, aluminum sulfate and aluminum citrate; The zirconium salt is selected from one or more of zirconium oxychloride, zirconium nitrate, zirconium sulfate and zirconium chloride; The surfactant is selected from one or more of sodium dodecylbenzene sulfonate, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, sodium lauryl sulfate and propylene glycol block polyether; The solvent is water and an alcohol solvent; the mass ratio of the water to the alcohol solvent is (2-5):
1.
8. The cross-linking agent according to claim 1, characterized in that The invention also comprises a pH regulator; the pH regulator makes the pH value of the mixed components be 4-7; the pH regulator is selected from one or more of sodium carbonate, sodium bicarbonate and sodium hydroxide.
9. A method for preparing a cross-linking agent, characterized in that: The following steps are involved: The metal salt, surfactant and solvent are mixed, and then heated to react, and then an organic ligand is added to continue the reaction to obtain a cross-linking agent.
10. A variable viscosity fracturing fluid, characterized in that: The invention comprises the cross-linking agent according to any one of claims 1 to 8 or the cross-linking agent prepared by the preparation method according to claim 9.
Citation Information
Patent Citations
Hypersalinity resistant cleaning thickening slick water, cross-linking agent, thickening resistance reducing agent and preparation method
CN110003877A
Hydrophobic association polyacrylamide suspension emulsion for fracturing and preparation method thereof
CN114456795A
Organic aluminum cross-linking agent, preparation method thereof and application of organic aluminum cross-linking agent in continuous mixed fracturing fluid
CN115287054A
Ultra-temperature organic zirconium crosslinker suitable for polymer crosslinking and prepared fracturing solutions of ultra-temperature organic zirconium crosslinker
CN102838781A
Crosslinking agent for polymer hydrofracturing fluid as well as preparation and application of crosslinking agent
CN103275690A